(untitled) (Research, Society and Development, 2020)
The antigens D, C, c, E, e, which are located in two proteins expressed in the red cell membrane: RhD (CD240D) and RhCE (CD240CE). The first protein is related to the D (Rh1) antigen and its variants, the second to the C, E, c, and (Rh2 to Rh5) antigens in various combinations (CE, cE, Ce and ce) and variants. The Rh system is made up of more than 56 antigens capable of producing hemolytic disease. D, C, c, E antigens are the main and most important antigens and are therefore called the system, based on the nomenclature described by Rosenfield. The work aims to analyze through scientific publications the association of the Rh system with hemolytic disease of the newborn. This is a qualitative bibliographic review based on scientific production based on studies already published. DHRN is characterized by the destruction of fetal erythrocytes by IgG class antibodies present in the maternal circulation. These specific antibodies against antigens present in the fetus’ red blood cells penetrate the placental barrier and promote the premature hemolytic process of erythrocytes, causing fetal anemia. This anemia has degrees that vary according to the intensity of the destruction of red blood cells. DHRN can present severe cases leading to anemia, increased bilirubin and organ involvement and therefore it is necessary that Rh negative mothers use immunoprevention measures with the use of polyclonal anti-D immunoglobulin.